Utilization of recombinase polymerase amplification combined with a lateral flow strip for detection of Perkinsus beihaiensis in the oyster Crassostrea hongkongensis - Lin Wu; Lingtong Ye; Zhaorui Wang; Yingyi Cui; Jiangyong Wang (Parasites & Vectors, 2019)
Abstract Background Perkinsosis, a disease caused by the protist Perkinsus, is responsible for mass mortalities of many molluscan species worldwide. The rapid, early and accurate detection of Perkinsus infection is necessary to react to outbreaks, and manage disease transmission. Current methods for diagnosis of Perkinsus spp. are time-consuming or require professional equipment and experienced personnel, rendering them unsuitable for field application. Recombinase polymerase amplification (RPA) assay is a highly sensitive and selective isothermal amplification technique that operates at temperatures of 37–42 °C, requires minimal sample preparation, and is capable of amplifying as low as 1–10 target DNA copies in less than 20 minutes. Methods We report a novel RPA assay that amplifies the internal transcriber spacer (ITS) region of P. beihaiensis, which, followed by rapid detection of amplicons using a lateral flow (LF) strip, enables easy visualization of results by the naked eye. Results The LF-RPA assay successfully amplified P. beihaiensis DNA using a set of primers of 20–25 bp in length. After incubation at 37 °C for 25 min, results were read within 5 min by the naked eye on a lateral flow strip. Our LF-RPA assay was comparably sensitive to qPCR assay, and capable of detecting as few as 26 copies of P. beihaiensis DNA. Cross-amplification occurred with other two Perkinsus species, P. olseni and P. chesapeaki, but not with other potential pathogen taxa in culture environments. We compared the performance of LF-RPA, conventional PCR and qPCR assays on 60 oyster samples. While LF-RPA assay results were 86.2% as sensitive, 77.4% as specific, and generally in agreement with those of conventional PCR results, they were more (93.3%) sensitive, (86.7%) specific, and agreed better with qPCR assay results. Future research should focus on developing simple DNA extraction methods that do not require professional laboratories and complicated extraction procedures, to facilitate application of this LF-RPA assay in the field. Conclusions Our LF-RPA assay provides a rapid and efficient method for detecting species of Perkinsus. This novel assay has potential to be used in field applications.